1994
DOI: 10.3354/meps113257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow-habitat on body size and reproductive patterns in the sea anemone Metridium senile in the Gullmarsfjord, Sweden

Abstract: In the Gullmarsfjord, on the west coast of Sweden, a variety of morphs of Metridium senile (L.) are found. A small form (pedal disc diameter 0.3 cm) is found in dense clones (90% coverage) in high-flow habitats at 2 to 5 m depth, and larger forms (pedal disc diameter = 2.5 to 3.5 cm) are found abundantly in subtidal low-flow habitats where body size increases with depth. In order to investigate the adaptive significance of body size and laceration in M senile from different current regimes, individuals of a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Anthony & Svane (1995) showed that substratum instability caused by moving mussels in a current-swept habitat significantly increased pedal laceration (fragmentation and clonal proliferation) in a subtidal population of the sea anemone Metridium senile. Larger forms of M. senile, with apparently higher clonal diversity, attached to rock walls in deeper sheltered localities compared with shallow current-swept mussel beds of Mytilus edulis (Anthony & Svane 1994). These observations parallel our own on C. muricata, and further emphasise habitat instability as an important factor in clonal proliferation of invertebrates.…”
Section: Spatial Variability In Sexual and Asexual Reproduction In Cosupporting
confidence: 82%
“…Anthony & Svane (1995) showed that substratum instability caused by moving mussels in a current-swept habitat significantly increased pedal laceration (fragmentation and clonal proliferation) in a subtidal population of the sea anemone Metridium senile. Larger forms of M. senile, with apparently higher clonal diversity, attached to rock walls in deeper sheltered localities compared with shallow current-swept mussel beds of Mytilus edulis (Anthony & Svane 1994). These observations parallel our own on C. muricata, and further emphasise habitat instability as an important factor in clonal proliferation of invertebrates.…”
Section: Spatial Variability In Sexual and Asexual Reproduction In Cosupporting
confidence: 82%
“…M. senile grew on hard substrates and appeared in two size-groups and several colour morphs (Anthony and Svane, 1994). Small red-brown individuals (pedal disc diameter (PDD)<20 mm) form mass aggregations in surface water down to 2 m. Small to large, reddish to white individuals (PDD up to 45 mm) grew solitary or in small presumed clones from the surface down to ca.…”
Section: Methodsmentioning
confidence: 99%
“…The nudibranch Aeolidia papillosa (Linnaeus, 1767) is the chief predator of the Swedish M. senile population (Wahl, 1985;Anthony and Svane, 1994). Acontia are long, thread-like structures filled with nematocysts.…”
Section: Introductionmentioning
confidence: 99%
“…Kaplan 1984), and in shallow (2 to 8 m deep) channels at Strommarna on the Swedish west coast, large subtidal beds of M. edulis are nearly 100% covered by populations of M. senile. Small body size (<2 cm pedal disc diameter, PDD) and high rates of pedal disc laceration (the mode of asexual reproduction in M. senile ;Bucklin 1987) are characteristic features of these populations of sea anemones (Anthony & Svane 1994). Larger forms of M. senile are found abundantly in sheltered and deeper localities attached directly to the rock wall and undergo pedal laceration at lower rates (see Anthony & Svane 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pedal laceration, and hence clonal growth, in Metridium senile may be stimulated by high current velocities, and differential size-frequency distributions between habitats are generally assumed to result from the effect of different current regimes, and/or genetically determined differences in rate of laceration among clones (Shick 1991, Anthony & Svane 1994. However, pedal disc laceration may also be a consequence of pedal disc locomotion in M. senile, and escape-recolonization events in pace with the dynamics within mussel patches are therefore likely to be imporlant features contributing to both individual (polyp) and clonal size of M. senile inhabiting mussel beds.…”
Section: Introductionmentioning
confidence: 99%